Global methylation patterns in primary plasma cell leukemia. (October 2018) - Todoerti, Katia; Calice, Giovanni; Trino, Stefania; Simeon, Vittorio; Lionetti, Marta; Manzoni, Martina; Fabris, Sonia; Barbieri, Marzia; Pompa, Alessandra; Baldini, Luca; Bollati, Valentina; Zoppoli, Pietro; et al.
Highlights: Primary plasma cell leukemia is characterized by a global hypomethylation. Genomic and epigenomic regions show different hypo/hypermethylation patterns. Main genomic lesions in pPCL are associated to differential methylation profiles. Significant correlated methylation-expression levels are observed for some genes. Several genes show lower methylation levels across MM disease progression. Abstract: Primary plasma cell leukemia (pPCL) is a rare and very aggressive variant of multiple myeloma (MM). Specific clinical, biological and molecular patterns distinguish pPCL from MM. Here, we performed a genome-wide methylation analysis by high-density array in 14 newly diagnosed pPCL patients along with 60 MMs, and 5 patients affected by monoclonal gammopathy of uncertain significance (MGUS). Our analysis revealed a global hypomethylation profile associated with pPCL. Additionally, differential methylation patterns were found related to distinct chromosomal aberrations and DIS3 mutations, affecting genes with roles in bone metabolism, cell migration, transcription regulation or DNA damage response. When compared with MM patients, pPCL showed a distinct methylation profile mostly characterized by hypomethylated probes specific for genes involved in several processes like cell adhesion and migration. Furthermore, decreasing methylation levels were evidenced for genes significantly modulated in the progressive phases of plasma cell dyscrasias, from MGUS to MM and pPCL. Overall, our data provide new insights into the molecular characterization of pPCL, thus being potentially useful in the prognostic stratification or identification of novel molecular targets.